Pengaruh Service Quality Terhadap Customer Satisfaction dan Customer Loyalty (Studi Kasus Pada LP3I Karang Tengah, Tangerang) - syukron sazly (Widya Cipta - Jurnal Sekretari dan Manajemen, 2018)
ABSTRACT  In the concept of service quality, customer satisfaction and customer loyalty is related to each  other. The level of  service quality which is the discrepancies between customer expectation and perception  will affect customer satisfaction  and customer satisfaction ensured to affect customer loyalty as well. And the level of service quality determined by a few variables where customer perceived and expected. The research analyzed  the existence of correlation and influence  between customer satisfaction and customer loyalty  at LP3I Karang Tengah, Tangerang, Banten Province. Connected with the Research Method , This research is descriptive quantitaTive research by asking responden to fill in the quessionaire that given, The respondena are the students of LP3I Karang Tengah who represent their level and their major. We use purposive sampling technic to collect  the data from 155 students of this  institution in the period of June 1–July 31, 2009 . The data  statistically has been analyzed by SPSS 16. with the  95 % significance degree. The variables which form customer satisfaction in this research are Tangible (X1) , Reliability (X2), Responsiveness (X3) , Assurance  (X4) and  Emphaty( X5) as Independent Variables  that adopted from servqual concept. Meanwhile , Relationship, Partnership and Ownership adopted from locking loyalty concept form customer loyalty( Y) as dependent variable. To know the normality of the data we use One-Sample Kolmogorov-Smirnov Test, and the result indicates the data is normal in distribution.. T-Test is used to test the impact of independent variable to dependent variable  partially. The Result, only Tangible (X1)  dan X3 (Responsiveness) partally  affect  significantly to  Loyalty (Y). F-Test is used to test the impact of independent variable to dependent variable simultanously. The Result,simultanously,  Tangible (X1) , Responsiveness (X3)  , Assurance  (X4) and  Emphaty( X5), affect  significantly to  Loyalty (Y). Meanwhile The Linier Regression Test resulted R suare  0.77, that  indicate  all variables of Customer Satisfaction affect  77 % significantly to  Customer Loyalty (Y). Keywords ; Service Quality,  Customer Satisfaction, Customer Loyalty